Optimal Monitoring and Sanctioning Systems - Conny Wunsch (Verein für Socialpolitik, 2010)
Many countries rely on monitoring of unemployment insurance and welfare recipients and impose benefit sanctions in case of noncompliance with job search requirements to encourage job search and to prevent abuse of the social insurance system. This paper systematically analyzes the characteristics of optimal monitoring and sanctioning systems for the unemployed as a function of worker characteristics, unemployment duration, the monitoring technology, worker preferences and the generosity of the welfare system. I propose a theoretical framework where benefits, wage taxes, the job search requirement, the monitoring intensity and the size of a benefit sanction are endogenously chosen by the planner for each period of unemployment. I allow for arbitrary ex-ante heterogeneity in reemployment wages and job finding probabilities as well as for dependence of these key parameters on unemployment duration. I find that the optimal sanction is in the majority of cases a temporary cut in benefits to zero, i.e. full suspension of benefits. The optimal monitoring intensity increases as the returns to search deteriorate with falling reemployment wages and job finding rates during unemployment in order to restore search incentives. It also increases with the generosity of the welfare system because monitoring can be used to offset some of the disincentives to search implied by more generous benefit payments. I also demonstrate how very informative and large data can be used to considerably improve and extend the insights that can be obtained from numerically solving and simulating economic models. I propose and apply a new method that allows quantifying the impact of implementing the optimal policy on the job finding probabilities. I find that the optimal policy implies considerably higher job finding rates than the actual policy, especially for low-skilled workers.
Keywords: J64; J65; J68; 330; Optimal unemployment insurance; monitoring and sanctions